THEORETICAL AND PRACTICAL CONSIDERATIONS ON THE IMPACT OF THE UNDERGROUND ECONOMY ON SUSTAINABLE ECONOMIC DEVELOPMENT - Elena HLACIUC (USV Annals of Economics and Public Administration, 2023)
The underground economy is a major challenge around the world and is a priority for many governments as it affects both developed and developing economies. The aim of this research is to address the concept of the underground economy and identify the effects of this phenomenon on the economy at the micro and macro level. In order to achieve the research aim, the following specific objectives were set: O1- to provide a current state of knowledge of the underground economy by referring to the relevant literature in the field; O2- to identify the peculiarities of the phenomenon of money laundering as a financial mechanism of the underground economy, O3- to analyse the tax system at international and national level as a determining factor in the development of the underground economy. In order to achieve the proposed aim and objectives, the research methodology used mixed research techniques, specific to qualitative and quantitative research. The results of the study demonstrate that the underground economy presents more risks than opportunities, as tax evasion, social injustice, economic distortions and associated institutional weakness outweigh the possible benefits, all of which can harm the business environment, competitiveness and equitable economic development. We believe that the study is particularly useful for international and national regulators to reconsider and adapt their tax policies to the current needs identified in this study in order to reduce the negative effects of the underground economy on economic development.